2019
DOI: 10.3946/kjme.2019.131
|View full text |Cite
|
Sign up to set email alerts
|

Development of e-learning in medical education: 10 years’ experience of Korean medical schools

Abstract: We aimed to explore medical students' online learning patterns and needs by analyzing data obtained from an e-learning portal of Korean medical schools. Methods: Data were obtained from learning resources and registered users of the e-learning portal by the consortium of 36 Korean medical schools, e-MedEdu (www.mededu.or.kr) over a period of 10 years. Data analytics were performed of its contents and usage patterns using descriptive statistics. Results: The website currently has over 1,600 resources, which hav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
48
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(50 citation statements)
references
References 20 publications
1
48
0
1
Order By: Relevance
“…From creating email and connecting via WhatsApp groups, now communication is mainly by web-based live video conferencing platforms (WebEx, Skype, Zoom, Microsoft Teams), and teaching web platforms (Moodle, Google Classrooms). The success of online education depends on addressing the disparity across learning resources, use of technology, communication tools and the ability to understand information from sources like computers and mobile phones 7,8 . A systematic review and meta-analysis from China in 2019 that included 16 articles observed no significant differences between online and offline learning.…”
Section: Introductionmentioning
confidence: 99%
“…From creating email and connecting via WhatsApp groups, now communication is mainly by web-based live video conferencing platforms (WebEx, Skype, Zoom, Microsoft Teams), and teaching web platforms (Moodle, Google Classrooms). The success of online education depends on addressing the disparity across learning resources, use of technology, communication tools and the ability to understand information from sources like computers and mobile phones 7,8 . A systematic review and meta-analysis from China in 2019 that included 16 articles observed no significant differences between online and offline learning.…”
Section: Introductionmentioning
confidence: 99%
“…During the past few months, e-Learning had become our sole and only option to ensures the continuity of higher education. Fortunately, eLearning has proven to be a successful adjunct and has de nitely impacted the environment in which medical students learn [5,6,7,8,9]. Our institution, as many others, started to embed the eLearning and blended learning into speci c courses.…”
Section: Introductionmentioning
confidence: 99%
“…Likewise, previous indicate that re ection and self-directed learning improve student OSCE scores [13,14]. e-Learning is becoming increasingly important in medical education and is an integral part of supporting medical students' self-directed learning as in MOOCs (Massive Open Online Courses) [15] and other online learning resources [16][17][18]. Still, research is scant on the impact of the use of e-learning for selfdirected learning to promote student clinical competencies and its impact on student performance in OSCEs.…”
Section: Introductionmentioning
confidence: 99%